Gene expression changes in response to field-to-lab transition in the Argentine ant, Linepithema humile. (August 2019) - Dittmann, Mathew; Buczkowski, Grzegorz; Scharf, Michael; Bennett, Gary
Graphical abstract: Highlights: Lab vs field Argentine ant colonies exhibit different gene expression patterns. Gene expression changes can arise within a month of living in the laboratory. Genes associated with laboratory living display intercorrelation of expression. Abstract: Gene expression research is a valuable tool for investigating how gene regulation and expression control the underlying behaviors that structure a eusocial insect colony. However, labs that focus on ant research frequently keep ant colonies in the lab for ease of sampling. It is typically impractical to accurately emulate the field conditions where ants are collected from, so laboratory colonies can be exposed to drastically different environmental conditions and food sources than they are naturally exposed to in the wild. These shifts in diet and environment can cause changes in the gene expression of the ants, affecting downstream behavioral and physiological systems. To examine the nature of these changes, colonies of the Argentine ant, Linepithema humile (Mayr, 1868), were excavated from North Carolina and transferred to the lab, where they were sampled monthly. Illumina and qPCR analyses were conducted on forager samples to detect any changes in gene expression. Approximately six percent of the Argentine ant genome, which represents 765 genes, showed changes in gene regulation after six months in the laboratory environment. The subset of these genes examined via qPCR show that the expression of many genes are correlated with each other, indicating that these genes might be a part of a regulatory network. These findings showed that ant colonies kept in the lab experience changes in gene expression, resulting in downstream effects. Therefore, lab ant colonies are not necessarily representative of wild colonies when conducting experiments on the gene expression, behavior, and physiology of these colonies.